INCREASING THE BUSINESS PERFORMANCE OF FOOD PROCESSING MSMES IN CIREBON BY CREATING COMPETITIVE ADVANTAGES THROUGH ENTREPRENEURSHIP ORIENTATION, DYNAMIC CAPABILITIES, AND MARKET ORIENTATION - Agus, Agus; Limakrisna, Nandan; Muharram, Hari (UTSAHA: Journal of Entrepreneurship, 2023)
MSMEs have contributed to accelerating economic growth and creating jobs. However, a number of problems still hinder the growth of their business performance. The improvement of business performance requires a competitive advantage that stems from a strong entrepreneurial and market orientation as well as the high dynamic capabilities of the actors in MSMEs. Therefore, this research aims to analyze the influence of these factors on competitive advantage and their impact on improving MSME business performance. A survey of 336 samples and a quantitative approach were conducted to prove the research hypothesis through structural equation modeling. The novelty of this research is the analysis of the determinants of competitive advantage, especially entrepreneurial orientation, dynamic capabilities, and market orientation, and their impact on business performance, as well as the mediating role of competitive advantage on the influences of entrepreneurial orientation, dynamic capabilities, and market orientation, respectively, on business performance. The study concluded that improving MSME business performance can be done by creating competitive advantage and dynamic capabilities in MSME actors. The creation of competitive advantage requires a strong entrepreneurial orientation and market orientation, as well as high dynamic capabilities by MSME actors. This study presents both theoretical and practical implications and research limitations.